Effect of Chronic Obstructive Pulmonary Disease on Airflow Motion Using Computational Fluid Dynamics Analysis - Nasrul Hadi, Johari; Jegatis, Balaiyah; Zulkifli, Ahmad (2014)
Chronic Obstructive Pulmonary Disease (COPD) ranked as the fifth leading cause of death in 2002 and it is had been predicted to become fourth leading cause of death worldwide by 2030. COPD is a disease that will narrow the airway progressively and it alters the behaviour of normal breathing flow. This study aims to investigate the changes of flow pattern and pressure distribution with respect the presence of COPD on the airway's lumen. Four airway models were generated based on the fifth to eighth generations of Weibel's lung model. The simulations were carried out using Reynolds number ranging of 200 to 1400, corresponding to an average height man breathing from rest to vigorous state. The three-dimensional (3D) incompressible laminar Navier-Stokes equations are solved using computational fluid dynamics (CFD) solver on unstructured tetrahedral meshes. This method overcomes the problem of the absence of actual images for different COPD locations. The simulation results show that the obstructed airways significantly alter the air flow rate ratio due to the recirculation happens at the obstructed model which prevents air to enter the lower generation. It is found that, as the Reynolds number increases, the pressure drop also increased drastically in obstructed airway.